Study on the geological stress sensitivity of weak geotechnical engineering in the Three Gorges reservoir area. Issue 2 (July 2021) - Qin, Yujia; Tang, Xin; Cheng, Longfei; Guo, Yuanchen; Yao, Lei; Li, Bin
Abstract: Soft rock has the characteristics of poor engineering mechanics, and it is easy to change under the action of water or external load. This paper uses the pulse attenuation permeability meter to develop permeability test and coefficient of variation for weak rock with common engineering mechanical properties. Calculate and explore the geological stress sensitivity characteristics of weak rock engineering within the Three Gorges reservoir area. The conclusions are as follows: the permeability of weak rock in the Three Gorges reservoir area is less than 0.1mD, which belongs to the type of compact soft rock, among which the permeability of medium sandstone (0.048mD)> the permeability of fine sandstone (0.0055mD)> the permeability of mud shale (0.0047mD); the rock permeability coefficient of variation is greater than 0.7, with a strong heterogeneity. The permeability of soft rock has obvious anisotropy. The permeability of the vertical layer of medium-fine sandstone and silty mudstone is greater than the permeability parallel to the plane. The difference between the two is closely related to the physical difference between different lithologies. The permeability of siltstone, shale and sandstone rocks decreases exponentially with the increase of effective stress. The relationship between the permeability loss rates of various types of rock is: shale> siltstone> sandstone, indicating the same stress condition, page Rocks have higher stress sensitivity than siltstones and sandstones. This is mainly because the fractures in sandstone and siltstone are more developed than shale.